The Influence of Job Satisfaction, Work Discipline, and Work Motivation on Organisational Commitment at CV. SENJA - Akmal Gibran Mursyidan; Andhika Mochamad Siddiq; Recky Recky (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Enhancing Organizational Commitment is a strategic imperative in Human Resource Management, considering the negative influence of low commitment on corporate performance amid intense industry competition. This study employed a quantitative verification method and multiple linear regression analysis on data collected from the complete employee population of 35 respondents at CV. SENJA through saturation sampling, with the objective of analyzing the empirical influences of Job Satisfaction, Work Discipline, and Work Motivation, and their influence on Organizational Commitment.  The analysis results indicate that all three factors significantly influence Organizational Commitment concurrently; however, only Job Satisfaction and Work Discipline are having a significant influence when analyzed singularly, while Work Motivation shows a positive yet statistically insignificant influence, indicating potential overlap with other variables in the model.  In conclusion, the management of CV. SENJA must prioritize the improvement of Job Satisfaction and Work Discipline, which will subsequently elevate Organizational Commitment.